2016
DOI: 10.1016/j.jid.2016.07.027
|View full text |Cite
|
Sign up to set email alerts
|

TSLP Down-Regulates S100A7 and ß-Defensin 2 Via the JAK2/STAT3-Dependent Mechanism

Abstract: Elevated T-helper type 2 cytokines in atopic skin, such as IL-4 and IL-13, were thought to be responsible for an impaired expression of antimicrobial proteins, which may contribute to the increased susceptibility to skin infections in patients with atopic dermatitis. In this study, the relationship between thymic stromal lymphopoietin and antimicrobial proteins and the involved molecular pathway was defined in normal human epidermal keratinocytes and human skin equivalent model. Stimulation of normal human epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Finally, we used the present findings about the IL‐13/periostin/IL‐24 pathway to clarify the underlying mechanism in AD patients. It has been already reported that expression of phosphorylated STAT6 and STAT3 and periostin is enhanced in skins of AD patients correlated with the severity of inflammation . However, no study dealing with IL‐24 expression has been thus far reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we used the present findings about the IL‐13/periostin/IL‐24 pathway to clarify the underlying mechanism in AD patients. It has been already reported that expression of phosphorylated STAT6 and STAT3 and periostin is enhanced in skins of AD patients correlated with the severity of inflammation . However, no study dealing with IL‐24 expression has been thus far reported.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that activation of STAT3 and STAT6 in keratinocytes is enhanced in skin of AD patients . IL‐4 or IL‐13 causes STAT6 activation, whereas several cytokines such as IL‐31, TSLP, and IL‐24, in addition to IL‐4 or IL‐13, activate STAT3 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, STAT3 may be a key regulator of filaggrin expression in human keratinocytes [31]. Our recent study showed that STAT3 was highly expressed in the skin of AD patients [32]. Other reports suggested the involvement of STAT3 in CLDN1 expression [33,34].…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that GM-CSF and TSLP are important players in STAT3 activation [35,36]. And the crosstalk between β-catenin and STAT3 signaling pathways has been reported in breast cancer stem cells [37].…”
Section: Arctigenin Inhibits Stat3/β-catenin Signaling Through Decreamentioning
confidence: 99%